2020
DOI: 10.1186/s13104-020-05332-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characteristics of rotavirus genotypes circulating in the south of Benin, 2016–2018

Abstract: Objective Rotavirus remains the main causative agent of gastroenteritis in young children in countries that have not yet introduced the vaccine. In Benin, rotavirus vaccine was introduced late December 2019 into the EPI. This study aims to provide pre-vaccination era rotavirus genotyping data in Benin. These data can supplement data from the surveillance system of Ministry of Health of Benin which is supported by the World Health Organization (WHO). Results Of the 420 diarrheal stool samples, actively collec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…Three atypical G9 strains from 2011 with G9P[4]I2-R2-C2-M2-A2-N2-T2-E6-H2 constellation was observed with rare E6-NSP4 gene. Similar reassortant strains of G9P[4] strains had been previously reported from India, Latin America and recently from Benin in 2016 [ 41 , 45 47 ]. In our study the rare E6 genotype was also observed with G1P[8] and G2P[4] strains during 2017 and 2012 respectively.…”
Section: Discussionsupporting
confidence: 78%
“…Three atypical G9 strains from 2011 with G9P[4]I2-R2-C2-M2-A2-N2-T2-E6-H2 constellation was observed with rare E6-NSP4 gene. Similar reassortant strains of G9P[4] strains had been previously reported from India, Latin America and recently from Benin in 2016 [ 41 , 45 47 ]. In our study the rare E6 genotype was also observed with G1P[8] and G2P[4] strains during 2017 and 2012 respectively.…”
Section: Discussionsupporting
confidence: 78%
“…A meta-analysis report by Leshem et al [94] did show evidence of low vaccine effectiveness against the heterologous strain in Latin America and Europe. Contrary to the significant decline of vaccine virus genotype and the increased frequency of detection of previously uncommon genotypes in South Africa, the human G1P [8] constellation remains predominant in countries such as Central African Republic and Benin where RV vaccine has not been fully established [25,102]. Additionally, the post-vaccination era also exhibited a significant increase of G2P [6] and G8P [4] species, with mosaic genotype constellation of human-animal origin, which were reported to be low in Benin [102].…”
Section: Discussionmentioning
confidence: 97%
“…Contrary to the significant decline of vaccine virus genotype and the increased frequency of detection of previously uncommon genotypes in South Africa, the human G1P [8] constellation remains predominant in countries such as Central African Republic and Benin where RV vaccine has not been fully established [25,102]. Additionally, the post-vaccination era also exhibited a significant increase of G2P [6] and G8P [4] species, with mosaic genotype constellation of human-animal origin, which were reported to be low in Benin [102]. The increase in rotavirus cases observed in the KwaZulu-Natal and Western Cape provinces despite the overall decline of diarrheal morbidity in the post-vaccine era may be explained, in part, by the accumulation of more strains that are heterotypic to vaccine types in a population, which was attributed to a higher disease burden in a meta-analysis from middle-income countries (Brazil, Colombia, Nicaragua, and Bolivia) [80].…”
Section: Discussionmentioning
confidence: 97%